Characterization of photovoltaic cells by spectral photocurrent measurements - Eyzaguirre, Carmen (1999)
At this Work, we present the first results of the colaboration UNI/HAHN-MEITNER-INSTITUT, obtained in the characterization of high efficiency solar cells (Programme Euro-Joule) with a home made photocurrent spectrometer. First, we show the application of the System to a monocrystalline silicon solar cell (Co. ISOFOTON /Spain). We describe next the results obtained with two types of "Joule"Solar cells: CdS/Cu(In,Ga,)(S,Se)2 and ZnSe/Cu(ln,Ga,)(S,Se)2.